Role of Chromodomain-Helicase-DNA-Binding Protein 4 (CHD4) in Breast Cancer - Novillo, Apolonia; Fernández-Santander, Ana; Gaibar, Maria; Galán, Miguel; Romero-Lorca, Alicia; El Abdellaoui-Soussi, Fadoua; Gómez-del Arco, Pablo (Frontiers in Oncology, 2021)
Chromodomain-helicase-DNA-binding protein 4 (CHD4) is an epigenetic regulator identified as an oncogenic element that may provide a novel therapeutic target for the treatment of breast cancer. CHD4 - the core component of the nucleosome remodeling and deacetylase (NuRD) complex - may be mutated in patients with this disease. However, information on CHD4 mutants that might allow their use as biomarkers of therapeutic success and prognosis is lacking. The present work examines the mutations in CHD4 reported in patients with breast cancer - as recorded in public databases - and attempts to identify their roles in its development. The databases revealed 81 point mutations across different types of breast cancer (19 of which also appeared in endometrial, intestinal, nervous system, kidney and lymphoid organ cancers). Some 71.6% of the detected mutations were missense mutations, 13.6% were silent, and 6.2% nonsense. Over 50% affected conserved residues of the ATPase motor (ATPase and helicase domains), and the domains of unknown function (DUF) in the C-terminal region. Thirty one mutations were classified by the examined databases as either 'deleterious', 'probably/possibly damaging' or as 'high/medium pathogenic'. Another five, nonsense, would have produced potentially harmful truncated proteins. Some mutations would seem to influence ATPase and DNA translocation activities (R1162W), while others would seem to alter protein stability (R877Q/H, R975H) or disrupt DNA binding and protein activity (R572*). According to the results of earlier in vitro and in vivo studies, some of the studied mutations may be involved in the development of breast cancer.